On-board-shell measurements of acceleration - Young, K.; Muirhead, R. (1991)
Rowing Performance as indicated by the acceleration profile of the shell and the rowing seat may be a sensitive diagnostic tool for the development and the teaching of good rowing. The thrust of the drive and the smoothness of the recovery are shown in extremely good detail by using on-board accelerometers on the rowing shell and the rowing seat. The qualitative measurements can yield some discoveries of the hydrodynamics of rowing. The quantitative measurements can also be used to verify the models of rowing. Further uses would be verify the efficacy of rowing styles and experimental equipment like rigging or of oars. The advent of good and rugged solid state accelerometers, and special purpose logging computers make this a practical device for field use.